2000
DOI: 10.1074/jbc.m002334200
|View full text |Cite
|
Sign up to set email alerts
|

CD47, a Ligand for the Macrophage Fusion Receptor, Participates in Macrophage Multinucleation

Abstract: The macrophage fusion receptor (MFR), also called P84/BIT/SIRP␣/SHPS-1, is a transmembrane glycoprotein that belongs to the superfamily of immunoglobulins. Previously, we showed that MFR expression is highly induced at the onset of fusion in macrophages, and that MFR appears to play a role in macrophagemacrophage adhesion/fusion leading to multinucleation. The recent finding that IAP/CD47 acts as a ligand for MFR led us to hypothesize that it interacts with CD47 at the onset of cell-cell fusion. CD47 is a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
162
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(171 citation statements)
references
References 36 publications
4
162
0
4
Order By: Relevance
“…MIAP410 was previously reported to not block mCD47-mSIRPα interactions (2). In contrast, we have determined that MIAP410 does block mCD47-mSIRPα interactions (Fig.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…MIAP410 was previously reported to not block mCD47-mSIRPα interactions (2). In contrast, we have determined that MIAP410 does block mCD47-mSIRPα interactions (Fig.…”
mentioning
confidence: 50%
“…1). This discrepancy may be attributable to the N-terminal GST-CD47 fusion protein used in the prior blocking assays (2). Polypeptide additions at the N terminus of CD47 prevent the N-terminal glutamine residue of CD47 from forming pyroglutamic acid.…”
mentioning
confidence: 90%
“…(13) Therefore, although the functions of osteoclasts and FBGCs differ, they express common molecules, such as DC-STAMP, that function in cell-cell fusion. (3) To date, various molecules have been identified that regulate fusion of osteoclasts or macrophages, including DC-STAMP, ATP6v0d2, CD47, CD44, CD9, CD81, MFR, E-cadherin, and meltrin-a (3,(14)(15)(16)(17)(18)(19)(20)(21) ATP6v0d2-deficient mice show significant reductions in fusion of either cell type. (21) DC-STAMP-deficient osteoclasts or FBGCs show a complete lack of cell-cell fusion, a function specific for macrophage lineage fusion, since fertilization and myotube formation is normal in DC-STAMP-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, we reported that the expression of macrophage fusion receptor/signal regulatory protein ␣ (MFR/ SIRP␣) is induced transiently in macrophages at the onset of fusion (9). MFR/SIRP␣ and its receptor, CD47, belong to the superfamily of immunoglobulins (IgSF), as does CD4, and their interaction plays a role in the recognition of self and in the fusion of macrophages (10). To gain further insight into the mechanism of macrophage fusion, we subjected fusing alveolar macrophages from rats to genome-wide oligonucleotide microarray analysis, and we discovered the expression of CD200 de novo at the onset of fusion.…”
mentioning
confidence: 99%